Hak Gugat bagi Pegawai Negeri Sipil (PNS) yang Diberhentikan Tidak dengan Hormat dengan Keputusan Tata Usaha Negara yang Didasarkan atas Putusan Pengadilan Tindak Pidana Korupsi - Kharis Maulana Riatno; Suprapto Suprapto (AHKAM, 2026)
Although the issue of dishonorable dismissal (PTDH) of Civil Servants (PNS) due to corruption crimes has been widely studied, research that specifically discusses the normative conflict between Supreme Court Circular Letter (SEMA) Number 5 of 2021 and Government Regulation Number 79 of 2021 concerning ASN’s right to sue remains limited. This study aims to analyze the legality of restricting PNS’s right to sue through SEMA Number 5 of 2021 and to formulate the ideal concept of access to justice in the state administrative law system. This study used a normative legal method with statutory, conceptual, and case approaches. Data were obtained through a literature study of primary and secondary legal materials, then analyzed qualitatively using prescriptive techniques. The results showed that the restriction of the right to sue through SEMA Number 5 of 2021 has the potential to create normative conflict, legal uncertainty, and restrictions on access to justice because it is not aligned with the right to legal remedies guaranteed under Government Regulation Number 79 of 2021. The findings also showed that PTDH decisions based on corruption criminal court decisions can still be reviewed in the state administrative court as long as the object of review is limited to administrative aspects. The conclusion of this study affirms that restricting PNS’s right to sue through the SEMA instrument needs to be positioned carefully so as not to reduce guarantees of legal protection in the state administrative law system. These findings imply the importance of harmonizing regulations on civil service dispute resolution and strengthening the concept of access to justice for ASN in obtaining fair, certain, and proportional legal protection.